The impact of Chinese outward investment: evidence from Cambodia and Vietnam - Julia Kubny; Hinrich Voss (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
This paper provides an initial qualitative assessment of the impact of China's Outward Foreign Direct Investment on local workers and firms in Cambodia and Vietnam. Based on interviews with 60 Chinese investors plus further interviews with other foreign investors and domestically owned firms in the manufacturing industries of the two countries, the study assesses employment and income effects, training, spillovers, and linkage effects.The analyses show that the positive effects of Chinese manufacturing investment have been limited, while negative effects have not been observed. Chinese firms have a strong positive impact on the domestic workforce, but little interaction with local firms, which reduces the potential gains from spillovers. This contrasts with UNCTAD's expectations, but is in line with findings on industrialised-country FDI and shows that the impact of any investment, whether or not Chinese, is constrained by existing host-country conditions. The findings suggest separate policy recommendations for the local economy in Cambodia and Vietnam to derive greater benefit from this investment.
Keywords: 330